2021
DOI: 10.1155/2021/9920826
|View full text |Cite
|
Sign up to set email alerts
|

Abrus precatorius Leaf Extract Reverses Alloxan/Nicotinamide-Induced Diabetes Mellitus in Rats through Hormonal (Insulin, GLP-1, and Glucagon) and Enzymatic (α-Amylase/α-Glucosidase) Modulation

Abstract: Background. Abrus precatorius is used in folk medicine across Afro-Asian regions of the world. Earlier, glucose lowering and pancreato-protective effects of Abrus precatorius leaf extract (APLE) was confirmed experimentally in STZ/nicotinamide-induced diabetic rats; however, the underlying mechanism of antidiabetic effect and pancreato-protection remained unknown. Objective. This study elucidated antidiabetic mechanisms and pancreato-protective effects of APLE in diabetic rats. Materials and Methods. APLE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…An ethanolic APLE was shown to reduce fasting blood glucose levels (BGL) in rats with chemically induced diabetes [7,8]. The reduction in BGL was 69 % (100 mg/ kg extract) compared to a reduction of 44 % by 300 mg/kg metformin, and was accompanied by increased serum insulin and glucagon-like peptide 1 (GLP-1) levels, reduced glucagon levels, inhibition of α-amylase and α-glucosidase, and improved recovery of damaged pancreatic β cells [7]. Our findings support the in vivo antidiabetic activity of A. precatorius leaves and demonstrates that increased skeletal muscle glucose uptake via the Akt/PI3K pathway is a mechanism responsible for the blood glucose-lowering action of APLE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An ethanolic APLE was shown to reduce fasting blood glucose levels (BGL) in rats with chemically induced diabetes [7,8]. The reduction in BGL was 69 % (100 mg/ kg extract) compared to a reduction of 44 % by 300 mg/kg metformin, and was accompanied by increased serum insulin and glucagon-like peptide 1 (GLP-1) levels, reduced glucagon levels, inhibition of α-amylase and α-glucosidase, and improved recovery of damaged pancreatic β cells [7]. Our findings support the in vivo antidiabetic activity of A. precatorius leaves and demonstrates that increased skeletal muscle glucose uptake via the Akt/PI3K pathway is a mechanism responsible for the blood glucose-lowering action of APLE.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research by others has demonstrated antidiabetic activity of APLE in diabetic animals. An ethanolic APLE was shown to reduce fasting blood glucose levels (BGL) in rats with chemically induced diabetes [7,8]. The reduction in BGL was 69 % (100 mg/ kg extract) compared to a reduction of 44 % by 300 mg/kg metformin, and was accompanied by increased serum insulin and glucagon-like peptide 1 (GLP-1) levels, reduced glucagon levels, inhibition of α-amylase and α-glucosidase, and improved recovery of damaged pancreatic β cells [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We separated retro-orbital blood into serum, and then detected total cholesterol (TC), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), high-density lipoprotein-cholesterol (HDL-C), and the aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio [ 38 ]. We used the enzyme-linked aptamer sorbent assay (ELASA) kit to measure serum INS, GLP-1, DDP-4 and inflammatory factors (Interleukin-10 (IL-10), Tumour necrosis factor alpha (TNF-α)) [ 39 , 40 , 41 ]. For the test, specimens, standards and HRP-labeled antibodies are added to microtiter wells pre-covered with antibodies, followed by incubation, washing, and color development.…”
Section: Methodsmentioning
confidence: 99%
“…Rats of both sexes were divided into 8 experimental groups and each group which comprised of 6 rats that were randomly divided at a ratio of 1:1 in each experimental group. The body weight of all animals ranged between (120 g–180 g) [ 78 , 79 ] and they ranged from 4–6 weeks old ( Figure 1 A). All animals were fed on normal feed and water.…”
Section: Methodsmentioning
confidence: 99%